Destruction du patrimoine et figure du soldat allemand dans les cartes postales de la Grande Guerre - Emmanuelle Danchin (Amnis)
The Great War’s illustrated postcards, specifically concerning topographical views of ruins, in spite of being a neglected source, can still reveal, even after reconstructions have long erased every trace of  war, the impacts of artillery and explosives on the civil, artistic and religious heritage, and on the housing environment. On either side of the western front, the French and the German have used these views of destruction as a testimony of the barbaric character of the enemy, thus contributing to the mobilization of the war population. A war of images, told through images, especially postcards, developed from 1914, becoming a sort of war within the war in which belligerents themselves took part. These views of ruins contributed to present the war as a war of civilisation against Kultur, and depicted the German as the ‘new barbarians’ perpetrators of cultural atrocities, displayed by the destruction of monuments. The German defended themselves against these accusations based on images of ruins; they produced postcards that emphasized the ‘barbarian’ terminology, understood in a new, positive light, the word then becoming a new distinctive and positive sign of self-representation. They also favoured the distribution of the views of ruins from the eastern front, thus designating the Russian as barbarians. The study of these representations of destruction introduces another approach on an aspect of the violence of cultural mobilisation.